FILM SERVICE PROBLEMS ON THE VIRGIN SOIL: STATISTICS AND EVERYDAY LIFE - O. V. Kuznetsova (Гуманитарные и юридические исследования)
The article studies topical issues of ilm servicing of virgin land areas in 1950-1960s in the light of an innovative complex micro and macro history approach. On the one hand, a detailed statistic analysis of the quantity of the mobile cinemas per each virgin land area is carried out. As well as the analysis of dynamic increase in the number of cinema units and the width of a scope by ilm sessions of virgin areas within the speciied period and the average attendance of ilm sessions by the virgin landers. On the other hand, cinema is considered from the point of view of a daily integral part of working virgin collective farms. The article features the memories and impressions of virgin landers about popular ilms and the place and value of cinema in their lives.